Absolute characteristics and conformation of cationic polymers by hydrodynamic approaches: Poly(AEMA-co-MAEMA-co-DMAEMA)stat copolymers. (December 2017) - Perevyazko, Igor; Trützschler, Anne-K.; Gubarev, Alexander; Lebedeva, Elena; Traeger, Anja; Tsvetkov, Nikolay; Schubert, Ulrich S.
Graphical abstract: Highlights: Novel cationic methacrylates were synthesized in a wide range of molar masses. A combined analytical approach was applied to study macromolecular characteristics. The absolute molar masses were determined by the sedimentation-diffusion analysis. The influence of the polymer α-end group on the solvation properties was discussed. The conformational parameters were evaluated for different solvent systems. Abstract: Сationic poly((2-aminoethyl)-methacrylate– co - N -methyl-(2-aminoethyl)-methacrylate- co - N, N- dimethyl-(2-aminoethyl)-methacrylate) copolymers were synthesized by reversible addition-fragmentation chain transfer polymerization in a wide range of molar masses 16, 000 < M, g mol - 1 < 130, 000 and narrow dispersities. The copolymers were investigated by a wide range of characterization techniques such as sedimentation velocity, intrinsic viscosity, translation diffusion, asymmetric flow field-flow fractionation, as well as standard SEC and NMR analysis. As a result a matrix of self-consistent parametric macromolecular characteristics and the absolute molar masses were obtained. Consistent Kuhn-Mark-Houwink-Sakurada scaling relationships were found for 0.2 M NaCl water ( [ η ] = 0.002 × M 0.85, s 0 = 0.0231 × M 0.41, D 0 = 2, 349 × M - 0.59 ) and 0.2 M NaOH water ( [ η ] = 0.022 × M 0.50 ) solvent system. The corresponding conformational characteristics of the macromolecules, that define the polymer behavior in solution – equilibrium rigidity and diameter of the polymer chain, were determined to be A = 4.3 nm and A = 1.1 nm for 0.2 M NaCl and 0.2 M NaOH respectively. Additionally, the anisotropic optical properties were studied by the flow birefringence revealing information about optical anisotropy of the monomer unit ( Δ a = - 1.5 × 10 - 25 cm 3 ). The presented study exemplifies the in-depth analytical characterization of cationic/charge polymers by the fundamental hydrodynamic approaches resolving the essential macromolecular characteristics and solution behavior.